2016
DOI: 10.5114/pg.2015.55185
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal healing after anti-TNF induction therapy predicts long-term response to one-year treatment in patients with ileocolonic Crohn’s disease naive to anti-TNF agents

Abstract: IntroductionObjective assessment of Crohn’s disease (CD) activity in patients treated with anti-tumour necrosis factor (anti-TNF) antibodies is crucial for the prediction of its long-term results. Mucosal healing estimated endoscopically has a strong predictive value; however, only combined assessment together with transmural healing in magnetic resonance enterography (MRE) gives full information about the whole spectrum of inflammatory lesions in CD.AimTo assess the usefulness of intestinal healing phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…Ripollés et al found that sonographic response after 12 and 52 weeks of treatment with biologics was predictive of good long‐term clinical outcomes. Eder et al demonstrated that the absence of transmural healing was associated with an almost 90% probability of exacerbation shortly after discontinuation of the anti‐TNF agent.…”
Section: Discussionmentioning
confidence: 99%
“…Ripollés et al found that sonographic response after 12 and 52 weeks of treatment with biologics was predictive of good long‐term clinical outcomes. Eder et al demonstrated that the absence of transmural healing was associated with an almost 90% probability of exacerbation shortly after discontinuation of the anti‐TNF agent.…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of these studies are detailed in Table 1 [ 13 - 15 , 41 - 44 ]. Three studies were prospective[ 15 , 41 , 44 ] and four were retrospective[ 13 , 14 , 42 , 43 ]. Only one study was performed in children[ 43 ].…”
Section: Transmural Healingmentioning
confidence: 99%
“…Only one study was performed in children[ 43 ]. The size of the study population ranged from 26[ 42 ] to 214[ 13 ] patients. Location of CD, defined by Montreal[ 45 ] or Paris[ 46 ] classification was as follows: ileocolon (L3)[ 42 ]; terminal ileum (± caecum) (L1) and ileocolon (L3)[ 13 , 14 , 44 ]; and, all types of location (L1, L2, L3 ± L4)[ 15 , 41 , 43 ].…”
Section: Transmural Healingmentioning
confidence: 99%
See 2 more Smart Citations